A Simple Flow Injection Spectrophotometric Procedure for Direct Determination of Copper(II) in Environmental Samples - Akmese, Bediha; Aydin, Rukiye; Asan, Adem (Asian Journal of Chemistry, 2014)
A new simple, rapid and sensitive flow-injection spectrophotometric detection method has been developed for the on-line determination of copper(II) in environmental water samples. The method is based on the measurement of the absorbance of the coloured complex formed by copper(II) with the Alizarin Red S (3,4-dihydroxy-9,10-dioxo-2-anthracenesulfonic acid sodium salt) in an acidic medium. The optimum conditions for the reaction of Cu(II) with Alizarin Red S is studied and the complex is selectively monitored at lmax 510 nm. With the reagent carrier solvent (3.5 × 10-5 M Alizarin Red S solution and 0.1 M acetate buffer, pH 5.0) flow-rate of 1 mL min-1. The calibration graph was linear in the Cu(II) concentration range 2-110 μg L-1 with the detection limit of 0.6 μg L-1 (RSD = 3.3 %, n = 6) was obtained at a sampling rate of 80 sample h-1. The detailed study of various interferences confirmed the high selectivity of the developed method. The proposed method was successfully applied to determination of copper(II) in real samples including river water and sea water. The accuracy of the method was demonstrated by the analysis of standard reference material MBH-C31XB20.